Robust strain sensor based on multimode interference in single-mode–multimode–single-mode fiber structure - Azmi, N.M.; Yusof, Nur Hotimah; Jusoh, Zulzilawati; Razak, Hashim Abdul; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2018)
Single-mode–multimode–single-mode (SMS) structure is demonstrated as a strain sensor. The device is fabricated by splicing a section of multimode optical fiber (MMF) in between single-mode fibers (SMFs). The modal interference inside the structure produces a strong resonant transmission notch, which is sensitive to external perturbation. It was found that the position of the notch changed with strain at sensitivity of 1.3 nm/N. The device introduced here is simple to fabricate, robust and suitable for high temperature operation; hence, it is adequate for diverse sensing applications.